Accessory scrotum in the perineum - Pananghat A Kumar; Pavai Arunachalam; Prasanna N Kumar (Wolters Kluwer Medknow Publications, 2011)
A case of accessory scrotum in a 2-day-old male infant is reported because of its rarity. An overview of sequences during the normal development of male external genitalia has been provided and the deranged mechanism resulting in this anomaly has been reviewed with hypotheses regarding etiology of accessory scrotum.